Preface: Unsolved problems of magnetospheric physics. Issue 11 (11th November 2016) - Denton, M. H.; Borovsky, J. E.; Stepanova, M.; Valdivia, J. A.
Abstract: The Unsolved Problems of Magnetospheric Physics Workshop was held in September 2015 in Scarborough, UK. In contrast to most other meetings, people were specifically asked not to present and discuss their recent results. Rather, they were asked to bring their opinions and thoughts on unsolved problems to the meeting. Short presentations were encouraged after which the audience would debate and discuss definitions of the problems and how they could be overcome. Were new observations required? New missions? Or simply did the community need to work better together to resolve pertinent and outstanding science questions? Around 50% of the meeting schedule was devoted to discussion sessions on these topics. Key Points: Many unsolved problems exist in magnetospheric physics The UPMP workshop discussed these problems and suggested possible solutions For some problems, the community already have the data and the tools to make rapid progress